Reliability of pathophysiological markers reflective of exercise-induced gastrointestinal syndrome (EIGS) in response to 2-h high-intensity interval exercise: A comprehensive methodological efficacy exploration - Young, Pascale; Russo, Isabella; Gill, Paul; Muir, Jane; Henry, Rebekah; Davidson, Zoe; Costa, Ricardo J. S. (Frontiers in Physiology, 2023)
The study aimed to determine the test-retest reliability of exercise-induced gastrointestinal syndrome (EIGS) biomarkers, and assess the association of pre-exercise short chain fatty acid concentration with these biomarkers in response to prolonged strenuous exercise. Thirty-four participants completed 2 h of high-intensity interval training (HIIT) on two separate occasions with at least 5-days washout. Blood samples were collected pre- and post-exercise, and analysed for biomarkers associated with EIGS [i.e., cortisol, intestinal fatty-acid binding protein (I-FABP), sCD14, lipopolysaccharide binding protein(LBP), leukocyte counts, in-vitro neutrophil function, and systemic inflammatory cytokine profile]. Fecal samples were collected pre-exercise on both occasions. In plasma and fecal samples, bacterial DNA concentration was determined by fluorometer quantification, microbial taxonomy by 16S rRNA amplicon sequencing, and SCFA concentration by gas-chromatography. In response to exercise, 2 h of HIIT modestly perturbed biomarkers indicative of EIGS, including inducing bacteremia (i.e., quantity and diversity). Reliability analysis using comparative tests, Cohen’s d, two-tailed correlation, and intraclass correlation coefficient (ICC) of resting biomarkers presented good-to-excellent for IL-1ra (r=0.710, ICC=0.92), IL-10 (r¬=0.665, ICC=0.73), cortisol (r=0.870, ICC=0.87) and LBP (r=0.813, ICC=0.76); moderate for total (r=0.839, ICC=0.44) and per cell (r=0.749, ICC=0.54) bacterially-stimulated elastase release, IL-1β (r=0.625, ICC=0.64), TNF-α (r=0.523, ICC=0.56), I-FABP (r=0.411, ICC=0.21), and sCD14 (r=0.409, ICC=0.38), plus fecal bacterial α-diversity; and poor for leukocyte (r=0.327, ICC=0.33) and neutrophil (r=0.352, ICC=0.32) counts. In addition, a medium negative correlation was observed between plasma butyrate and I-FABP (r= -0.390). The current data suggest a suite of biomarkers should be used to determine the incidence and severity of EIGS. Moreover, determination of plasma and/or fecal SCFA may provide some insight into the mechanistic aspects of EIGS instigation and magnitude in response to exercise.